2021
DOI: 10.12703/r/10-44
|View full text |Cite
|
Sign up to set email alerts
|

Anabolic treatments for osteoporosis in postmenopausal women

Abstract: Antiresorptive agents are generally recommended as first-line treatment for osteoporosis in postmenopausal women. These drugs suppress bone resorption but do not rebuild bone, limiting their efficacy. Antiresorptive use is further hampered by concerns over rare side effects, including atypical femoral fractures and osteonecrosis of the jaw. Anabolic treatments overcome limitations of antiresorptive treatment by stimulating new bone formation, reducing the risk of fracture with greater efficacy. This review sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 63 publications
(64 reference statements)
0
15
0
Order By: Relevance
“… 652 Conventional treatments for osteoporosis are currently divided into two groups: on the one hand, antiresorptive drugs that act directly on osteoclasts, limiting their activity and thus increasing bone mass and bone strength; 653 and on the other hand, anabolic agents that act on osteoblasts, increasing bone formation and reversing the loss of bone mass. 604 However, although these currently used pharmacological therapies are effective in decreasing the fracture risk and improving bone mineral density, they have some limitations related to bioavailability and toxicity issues in non-skeletal tissues, and cannot offer long-term solutions.…”
Section: Potential Biomedical Treatments Using Msnsmentioning
confidence: 99%
See 1 more Smart Citation
“… 652 Conventional treatments for osteoporosis are currently divided into two groups: on the one hand, antiresorptive drugs that act directly on osteoclasts, limiting their activity and thus increasing bone mass and bone strength; 653 and on the other hand, anabolic agents that act on osteoblasts, increasing bone formation and reversing the loss of bone mass. 604 However, although these currently used pharmacological therapies are effective in decreasing the fracture risk and improving bone mineral density, they have some limitations related to bioavailability and toxicity issues in non-skeletal tissues, and cannot offer long-term solutions.…”
Section: Potential Biomedical Treatments Using Msnsmentioning
confidence: 99%
“…600 In addition, the treatment of diseases such as osteoporosis or osteosarcoma, even if effective in reducing the risk of fracture or increasing the survival rate, respectively, also has certain limitations such as bioavailability, tissue specificity, long-term effect or development of resistance. 597,598,600,604,605…”
Section: Potential Biomedical Treatments Using Msnsmentioning
confidence: 99%
“…In the general population, anabolic therapy is effective at improving BMD and more effective than antiresorptive therapy at preventing fracture. 39…”
Section: How Should We Manage Individuals Receiving Pd At High Risk O...mentioning
confidence: 99%
“…In the general population, anabolic therapy is effective at improving BMD and more effective than antiresorptive therapy at preventing fracture. 39 Teriparatide, a PTH analogue, has been used in case reports of individuals receiving dialysis with biopsyproven adynamic bone disease. Three small studies of 7-22 patients with low PTH (<6.5 pmol/L in two studies) showed an improvement in BMD over 1-2 years at the lumbar spine but not the femoral neck.…”
Section: Anabolic Therapymentioning
confidence: 99%
“…Most of these drugs have been reported to be effective in reducing the risk of fracture in placebo-controlled studies despite slight differences. The use of anti-osteoporotic drugs has been reported to reduce the relative fracture risk of osteoporosis to 40%–73% in vertebral fractures and 40%–53% in hip fractures [ 4 5 ]. The mechanisms and characteristics of each drug vary; hence, the sequential application of osteoporosis drugs may lead to varying effects.…”
Section: The Rationale For the Sequential Treatment Approach In Osteo...mentioning
confidence: 99%